Efficiency measurement of grocery retail warehouses with DEA - Andreas Gafner; Dominic Loske; Matthias Klumpp (Adapting to the Future: Maritime and City Logistics in the Context of Digitalization and Sustainability. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 32, 2021)
Purpose: To enable reliable food supply and to remain competitive, grocery retailers need to operate efficient distribution networks. Therefore, the purpose of this paper is to develop and apply a multi-criteria evaluation framework considering the complexity of grocery retail warehouses while maintaining the highest possible efficiency. Methodology: We propose data envelopment analysis (DEA) as a non-parametric method of efficiency measurement and use an empirical seven-year dataset of 12 grocery retail warehouses. Four inputs and six outputs are included. We examine the efficiency development with DEA window analysis for longitudinal efficiency evaluation. By adding super efficiency, the model gains discriminatory power for efficient warehouses. We provide concrete improvement targets for all non-efficient warehouses through slack-based measurement. Findings: As a method for multi-criteria efficiency evaluation, DEA models provide interesting results for efficiency measurement in food supply chains. Through the non-parametric multi-criteria approach, it enables an objective and holistic analysis perspective. By choosing inputs and outputs independently of their measurement unit, flexible application possibilities appear, giving non-monetary elements the necessary importance in optimization. Originality: Although there are several studies dealing with the efficiency measurement of warehouses using DEA, our approach is the first to explore its application in food retail warehouse logistics over several periods.
urn:nbn:de:gbv:830-882.0162355; hdl:10419/249609; https://econpapers.repec.org/RePEc:zbw:hiclpr:32
Keywords: 650; HICL and Practice; Excellence in Logistics and Supply Chain Management